The mystery in the computer game - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (Morton Grove, Ill. : A. Whitman, 2000)
The children visit a computer game company and solve the mystery of computer game that uses people and places in real life.
520
Accelerated Reader AR
Keywords: Computers -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories; Fiction